2017
DOI: 10.1002/hlca.201700172
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Synthesis of Lepidocrocite‐Containing Material and Its Catalytic Behaviour in CO Oxidation

Abstract: Leptothrix sp. was cultivated in Lieske's medium in the presence of Al foil covered by anodic Alumina. Samples of biomass deposited on lamellae were studied by the methods of infrared, Mössbauer, and X‐ray photoelectron spectroscopy. Sole deposition of γ‐FeOOH on the lamellae was found to take place. This result is explained by the influence of γ‐AlOOH ingredient in the used support due to crystal structure similarity. Thus, iron oxyhydroxide crystallisation could be directed during bacteria cultivation. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Also, it was observed that iron oxyhydroxide crystallization could be directed during the cultivation of Leptothrix sp. bacterium [ 73 ]. The formation of strongly magnetic nanoscale particles due to lepidocrocite bioreduction by the iron-reducing bacterium Shewanella putrefaciens ATCC 8071 is described in [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, it was observed that iron oxyhydroxide crystallization could be directed during the cultivation of Leptothrix sp. bacterium [ 73 ]. The formation of strongly magnetic nanoscale particles due to lepidocrocite bioreduction by the iron-reducing bacterium Shewanella putrefaciens ATCC 8071 is described in [ 74 ].…”
Section: Discussionmentioning
confidence: 99%